2016
DOI: 10.3389/fnins.2016.00019
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Noise in Coupling Strength and Natural Frequency within a Pacemaker Network; Consequences for Development of Intestinal Motor Patterns According to a Weakly Coupled Phase Oscillator Model

Abstract: Pacemaker activities generated by networks of interstitial cells of Cajal (ICC), in conjunction with the enteric nervous system, orchestrate most motor patterns in the gastrointestinal tract. It was our objective to understand the role of network features of ICC associated with the myenteric plexus (ICC-MP) in the shaping of motor patterns of the small intestine. To that end, a model of weakly coupled oscillators (oscillators influence each other's phase but not amplitude) was created with most parameters deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 63 publications
2
62
0
Order By: Relevance
“…We consider the disordered slow wave patterns observed in this study to likely be a normal physiological response to the intra‐operative experimental conditions, although these may not be reflective of normal in vivo , fed‐state physiology. The multiple dynamic pacemakers observed in this study could be reflective of normal intestinal function where a dynamic network of multiple pacemakers is known to play an important functional role, for example in segmentation . However, the degree and complexity of the disordered propagation could also be abnormal initiation and conduction, possibly due to intestinal handling or anesthesia, particularly because intestinal slow waves have been previously shown to entrain over much longer plateau distances .…”
Section: Discussionmentioning
confidence: 80%
“…We consider the disordered slow wave patterns observed in this study to likely be a normal physiological response to the intra‐operative experimental conditions, although these may not be reflective of normal in vivo , fed‐state physiology. The multiple dynamic pacemakers observed in this study could be reflective of normal intestinal function where a dynamic network of multiple pacemakers is known to play an important functional role, for example in segmentation . However, the degree and complexity of the disordered propagation could also be abnormal initiation and conduction, possibly due to intestinal handling or anesthesia, particularly because intestinal slow waves have been previously shown to entrain over much longer plateau distances .…”
Section: Discussionmentioning
confidence: 80%
“…Values of both ϕ and τ were normalized to T , the undisturbed contraction interval measured as the average of several full cycles before the pulse. Contraction waves always travelled distally, owing to the ICC natural frequency gradient (Parsons & Huizinga, , ). Therefore as each contraction wave approached the pulse time, ϕ decreased while d increased, generating a diagonal line of sample points across the (ϕ, d ) plane (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The propagating haustral boundary contractions have a very strong, stable rhythmicity at 0.5 cpm and can both be antegrade and be retrograde propagating. When an antegrade and a retrograde wave collide, both are annihilated, a feature that suggests a network of coupled oscillators underlying them . Several studies have concluded that the rhythmic propagation of the haustral boundaries is likely facilitated by ICC‐generated slow waves, an example of a neurally activated slow wave, hence a stimulus‐dependent slow wave .…”
Section: Discussionmentioning
confidence: 99%